Recent Improvements in CRISPR-Based Amplification-Free Pathogen Detection - Zhang, Jian; Lv, Hailong; Li, Linxian; Chen, Minjie; Gu, Dayong; Wang, Jin; Xu, Yong (Frontiers in Microbiology, 2021)
Molecular diagnostic (MDx) methods directly detect target nucleic acid sequences and are therefore an important approach for precise diagnosis of pathogen infection. In comparison with traditional MDx techniques such as PCR, the recently developed CRISPR-based diagnostic technologies, which employ the single-stranded nucleic acid trans-cleavage activities of either Cas12 or Cas13, show merits in both sensitivity and specificity and therefore have great potential in both pathogen detection and beyond. With more and more efforts in improving both the CRISPR trans-cleavage efficiencies and the signal detection sensitivities, CRISPR-based direct detection of target nucleic acids without pre-amplification can be a possibility. Here in this mini-review, we summarize recent research progresses of amplification-free CRISPR-Dx systems and explore the potential changes they will lead to pathogen diagnosis. In addition, discussion of the challenges for both detection sensitivity and cost of the amplification-free systems will also be covered.